Electronic banking and treasury security - Welch, Brian (CRC Press : Woodhead Pub. and the Association of Corporate Treasurers, 1999)
This edition takes into account the very latest advances in electronic banking and treasury security. The electronic transmission of funds from companies to banks means that companies are responsible for high levels of risk previously covered by the bank's own security systems. This book is the definitive source of advice for all finance professionals. Electronic banking and treasury security covers everything from the systems themselves to the new documentation and includes contributions from leading figures in the banking, treasury and computing communities. This book is invaluable to corporate treasurers, finance directors, bankers and the financial advisory community.